Editorial: Purchasing and innovation: Past, present and future of the field of research. Issue 2 (March 2022) - Johnsen, Thomas; Le Dain, Marie-Anne; Kiratli, Nadine; Schiele, Holger
Abstract: This paper introduces the special topic forum (STF) on purchasing and innovation. Presenting the findings from a systematic literature review, we take stock of the current state of the field, delineating themes, theories and methods, and identifying key trends over time. Our study shows a take-off in research on purchasing and innovation during the last decade. This has predominantly focused on private sector manufacturing firms although a recent expansion into public sector research is evident. Large-scale surveys and case studies are still the dominant research methods where the unit of analysis is typically the 'firm' or 'project'. The findings also show how in the past the field was driven by questions on how purchasing can facilitate different types of innovation projects, seeking to derive practical implications, and rarely making explicit statements regarding theories applied; this still characterises much of the research but we find an increasing focus on theory development. We also see a shift in the type of technological innovation being investigated: past studies tended to focus on the role of purchasing in new product development (NPD) projects, which reflected a relatively low degree of technological uncertainty, but we see a trend towards innovation projects facing technological uncertainty. Research shows how this requires new ways of sourcing innovations and therefore new ways for purchasing to facilitate innovation sourcing. On the basis of the review, we offer our guidance for future research avenues to 1) carry out more research on procurement of innovation in the public sector; 2) consider new theories and research methods, and 3) go beyond firm-level or dyadic analysis to research networks and ecosystems. We conclude by introducing the papers in the STF.